Method for modifying polymeric supports, polymeric supports obtained by such methods, chromatography columns, chromatographic separation methods and uses of polymeric supports - Patents.com
Patent Information
- Application Number
- JP2023538112
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-22
- Filing Date
- 2021-12-21
- Publication Date
- 2024-12-27
AI Technical Summary
Existing ion exchange chromatography materials face challenges in independently adjusting hydrophilicity, capacity, and selectivity, leading to inconsistent performance and limited applicability, especially when using hydroxide eluents.
A method involving sequential coating of polymeric supports with oligoamines or polyamines, followed by the introduction of epoxy groups and quaternary ammonium groups, allows for independent adjustment of hydrophilicity, capacity, and selectivity, using materials like polyethyleneimine (PEI) to enhance stability and reproducibility.
The method produces highly reproducible, mechanically stable ion exchange materials that can separate a wide range of ions effectively, including haloacetic acids, with improved selectivity and capacity, suitable for both anion and cation exchange chromatography.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for modifying a polymeric support for use as a stationary phase in an analytical or preparative process. The present invention further relates to a polymeric support obtained by such a method. The present invention further relates to a chromatography column packed with the polymeric support, to a method for the chromatographic separation of analytes, and to the use of such a polymeric support for the separation of analytes, in particular in anion exchange chromatography, cation exchange chromatography and / or HILIC chromatography. [Background technology]
[0002] Ion exchangers are usually made of particulate materials that carry a charge on their surface, allowing them to retain ions. Anion exchangers are often based on cationic ammonium compounds, but phosphonium and arsonium ions are also known. For pure electrostatic interactions, the retention time is determined by Coulomb's law. Therefore, only the anion charge should affect its retention time. However, when ion chromatography is performed in aqueous solutions, other factors affect the retention behavior, such as the hydration of the anions and the hydration of the exchange groups. The polarizability of the ions involved and weaker secondary interactions between the analyte and the exchange substrate also play a role.
[0003] Carbonate and hydroxide solutions are the most common eluents used in suppressed anion exchange chromatography, but in the last decade the trend has shifted increasingly towards the development of hydroxide-selective anion exchange columns. The advantages of hydroxide eluents compared to carbonate eluents are: the ability to use gradient elution for simultaneous separation of weakly and strongly retained compounds, lower background conductivity and therefore higher sensitivity of the analysis. Another advantage is that hydroxide eluents provide better resolution of fluoride ions from the void volume, which is often a problem when using carbonate eluents. Also, some standards for monitoring disinfection by-products in water recommend hydroxide eluents.
[0004] Columns for use in suppressed IC mode with hydroxide eluents should be stable at high pH up to 14 and are usually prepared using aromatic substrates, e.g., DVB-based copolymers, with high surface hydrophilicity provided by the respective anion exchange coating V, increasing the elution power of hydroxide ions and column efficiency for highly polarizable anions, e.g., nitrate, iodide, perchlorate, etc.
[0005] Packing materials based on aromatic copolymers with hydrophilic anion exchange coatings are disclosed in Analytica Chimica Acta, Vol. 964 (2017) p. 187. This reference describes PS-DVB-based anion exchangers formed by reacting an anion exchange coating, bound to a substrate by the linker 1,4-butanediol diglycidyl ether, with 1,4-butanediol diglycidyl ether to bind polyethyleneimine, crosslinking it and quaternizing it. Although such materials have fairly good selectivity for the separation of standard inorganic anions and some organic acids, the capacity of the resin is determined by the degree of crosslinking between polyethyleneimine and 1,4-butanediol diglycidyl ether and therefore cannot be adjusted independently of the column selectivity in the proposed manufacturing method.
[0006] A very similar packing material with a polyethyleneimine-based coating is disclosed in WO 2020 / 044813 A1, where the polyethyleneimine-coated substrate is then reacted with diglycidyl ether and tertiary amine. However, in the proposed approach, the desired functionality is only formed when a certain ratio of polyethyleneimine to diglycidyl ether is used, and crosslinking is highly probable under the described reaction conditions. This affects selectivity and creates additional capacity due to the inevitable quaternization of the amino groups of polyethyleneimine, and therefore selectivity and capacity cannot be changed independently. Also, the early elution of divalent sulfate ions on the reported packing material under optimized test conditions may be due to the presence of nearby analytes (e.g., ClO3) that are present in much lower amounts in real samples. - and NO2 - This can raise questions about the quantification of
[0007] Another method for producing hydrophilic coatings for aromatic substrates used with hydroxide eluents in suppressed ion chromatography was proposed in Journal of Chromatography A1213 (2008) 37 and US Patent Application Publication No. 2005 / 0181224, which involves the stepwise growth of a positively charged highly branched layer on the surface of sulfonated EVB-DVB by repeating modification cycles involving the reaction of primary amines with diglycidyl ethers. The produced materials have good selectivity and high capacity, which can be increased by increasing the number of modification cycles (degree of branching). However, increasing the number of cycles leads to changes in the capacity as well as the selectivity, since the crosslinking process becomes more likely. Therefore, these parameters cannot be controlled independently of each other. Also, the production of such coatings that lead to good selectivity involves many synthesis steps (usually more than 8), which makes the reproducibility of the coating more difficult.
[0008] Attempts have been made to provide particularly stable support particles, preferably support particles with a hydrophobic core that can be (surface) modified to achieve certain desired properties in separation processes.For example, PCT / EP2020 / 059908 teaches modified support materials for use in separation methods, with adjustable hydrophilicity, balanced capacity, a large number of theoretical plates, chemical inertness, and high mechanical stability.The modified support materials according to the above documents work well in ion chromatography separations using carbonate eluents, but the use of hydroxide eluents leads to co-elution of some two analytes that are well resolved with carbonate, which limits the applicability of such materials to solve major analytical problems in industry.
[0009] US Patent Publication No. 2008 / 203029 discloses a polymeric chromatographic medium for bioseparation, produced by using polymer particles derivatized with polyethyleneimine that are further functionalized with an appropriate reactant. EP2060316 discloses a medium for chromatographic applications, the medium being a membrane for chromatographic purification of viruses, with a surface coated with polyethyleneimine. The immobilized PEI is modified with a charge modifier to impart quaternary ammonium functionality to the medium. CN105396628 relates to 2,3-epoxypropyltrimethylammonium chloride modified PEI graft modified PS / DVB ion chromatographic packing. The PS / DVB microspheres function as a carrier substrate. They are first modified with methacrylic acid glycidyl ester to provide epoxy groups for further reaction steps. US Patent No. 6,780,327 provides a positively charged microporous membrane comprising a hydrophilic porous substrate and a crosslinked coating comprising pendant cationic groups. None of these documents provide mechanically and chemically stable particles that are suitable for ion exchange chromatography and are produced in such a way that hydrophilicity, capacity, and selectivity can be configured independently of each other. Summary of the Invention [Problem to be solved by the invention]
[0010] The object of the present invention is to overcome the disadvantages of the state of the art. In particular, the object of the present invention is to provide a polymeric support modified such that the hydrophilicity of the material can be adjusted independently of the oxygen content of the polymeric core substrate, resulting in mechanically stable and robust particles while providing largely reproducible properties between batches. Furthermore, an ion exchanger based on a polymeric support should be provided that is chemically largely inert, and the hydrophilicity, capacity and selectivity can be configured independently of each other. [Means for solving the problem]
[0011] The object is achieved by a modification method, a polymeric support, a chromatography column, a separation method and the use of a polymeric support having the features of the independent claims. However, the applicability of the invention is not limited to hydroxide eluents only.
[0012] A first aspect of the present invention relates to a method for modifying a support material, in particular a polymeric support material, for use as a stationary phase in an analytical or preparative process, the method comprising the steps of: a) providing a support; b) coating the support with an oligoamine or polyamine; and c) Support material - a first functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups, and - ion exchange groups, preferably quaternary organic elements of main group V, preferably quaternary ammonium groups with a compound comprising Includes.
[0013] Steps b) and c) can be carried out sequentially or simultaneously, preferably sequentially. For simultaneous implementation, the support material is mixed in one step with the oligo- or polyamine and the compound comprising a first functional group, preferably an epoxy group, reactive with amine and / or hydroxyl groups, and an ion-exchange group, preferably a quaternary organic element of main group V, preferably a quaternary ammonium group. Alternatively, in a first step, the oligo- or polyamine is mixed with the compound comprising a first functional group, preferably an epoxy group, reactive with amine and / or hydroxyl groups, and an ion-exchange group, preferably a quaternary organic element of main group V, preferably a quaternary ammonium group, and in a second step, the support material is added to the mixture.
[0014] The coating in step b) may be a covalent coating or an electrostatic coating. As outlined in more detail below, the support material provided in step a) is preferably either directly coated with the polyamine or a spacer can be provided between the support material and the polyamine. The polyamine can be selected from the group consisting of polyallylamine, linear or branched polyethyleneimine (PEI), poly(2-methylaziridine), preferably branched PEI. Branched PEI can be used, particularly preferably with an average molecular weight Mw of 600-1800 Da (by light scattering LS) and an average Mn of 400-1600 Da (by gel permeation chromatography GPC). Each molecule of PEI can have several attachment points, since several amine groups of one molecule can react with groups that are reactive with amine groups. The reactive groups can be provided by the support material provided in step a.
[0015] The advantage of the method according to the invention is that highly reproducible polymer supports can be obtained: the previous step of hydrophilizing the surface of the hydrophobic core due to the amine coating, especially the PEI coating, has only a minimal effect on the properties and performance of the resulting material, while still resulting in mechanically stable and robust particles.
[0016] A particular advantage of the polymeric support is that it can be further processed to be used as the stationary phase of anion exchange chromatography.However, the use of the particles is by no means limited to this.Alternatively, the particles can be used in other analytical and preparative methods, such as cation exchange chromatography, other adsorption chromatography methods, HILIC chromatography (hydrophilic interaction liquid chromatography), reverse phase chromatography, solid phase extraction, etc.
[0017] Hydrophilicity, capacity and selectivity are independently adjustable in such ion exchange materials. The ion exchange groups are charged groups on the surface of the polymeric support, especially charged amine or phosphine groups, especially quaternary ammonium groups.
[0018] By varying the amount of ion exchange groups, the capacity of the separation material can be adjusted and moderated, and the support material is converted into a material suitable for ion exchange interactions, particularly ion exchange chromatography.
[0019] Due to the reaction with PEI, the capacity and selectivity of ion exchange materials based on polymer supports can be adjusted independently of each other.
[0020] In addition, due to the reaction with PEI, the ion exchanger material based on the aforementioned polymeric support avoids the problematic co-elution with oxohalides and certain haloacetic acids, such as DCA (dichloroacetic acid), MCA (monochloroacetic acid), MBA (monobromoacetic acid), DCA (dichloroacetic acid), DBA (dibromoacetic acid), TCA (trichloroacetic acid). In fact, the polymeric support according to the invention can serve as a substrate for producing anion exchangers that allow the separation of five haloacetic acids, in addition to inorganic standard ions and oxohalides, preferably by using gradient elution with KOH. To the best of the inventor's knowledge, ClO2 - , MCA, BrO3 -A column that provides baseline separation of , and MBA is reported for the first time.
[0021] Some other problems claimed in the art can also be overcome. The effect of coating the polymer particles mainly with 1,4-BDDGE turns out to be rather dominant, and therefore the selectivity towards inorganic anions is difficult to control. These problems are solved by the support material disclosed in the present invention. The tendency of DCA to co-elute with chlorate ions (in KOH eluent, methylmorpholine (MM)-quaternized material) is improved. Similar problems that appear when chlorite and bromate ions are separated in the presence of other functionalities (N-methylpyrrolidone (NMP), N-methyl-diethanolamine (MDEA)) are overcome by the support material disclosed in the present invention. In particular, Br - , NO3 - , ClO3 - , and the challenge of controlling selectivity for DCA was alleviated.
[0022] By using polymeric supports as ion exchange stationary phases, high theoretical plates per column meter (>50000 TP / m) for seven standard anions (fluoride, chloride, nitrite, bromide, nitrate, phosphate, and sulfate) can be obtained with high signal symmetry (asymmetry <1.5). All the aforementioned ions exhibit separate baselines in the chromatograms with short overall chromatographic run times.
[0023] Preferably, following step c), the reaction product resulting from step c) is reacted with one or more polyfunctional compounds, in particular at least one first functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups, and - at least one second functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups; A cross-linking step d) is carried out by treating the compound with
[0024] This step causes a significant shift in selectivity in the chromatograms obtained with these ion exchangers. - / NO3 - and DCA / ClO3 - The resolution of is made possible and optimized by using the polymer support obtained after step d) as ion exchange material, especially in a KOH eluent.
[0025] It is particularly preferred that steps b), c) and d) are performed sequentially in the order indicated. If step d) is performed before step c) in a sequential process, the capacity will be extremely low and all ions of interest will co-elute with each other. This is due to the lack of available reactive sites for ion-exchange moieties when the polymeric material first reacts with the crosslinker molecules. The availability of these sites is reduced by the covalent attachment of the crosslinker molecules to the PEI, and the crosslinking results in the formation of a shell network, blocking the PEI from reacting with the ion-exchange molecules.
[0026] If steps b), c) and d) are carried out simultaneously, for example in a one-pot reaction with a polyamine having a molecular weight between 600 Da and 1800 Da, and with a reaction time such that 0.90-1.33% N, preferably 1.00-1.28% N, particularly preferably 1.15-1.25% N, reacts on the polymeric material, the resulting polymeric support gives a chromatogram in which DCA, chlorate and bromide ions co-elute, and chlorite ions co-elute with bromate ions. The co-elutes may be dissolved by the material obtained from the sequential process. Furthermore, the capacity is lower in the simultaneous process and the product is less reproducible compared to the product obtained from the sequential process.
[0027] If steps b) and c) are carried out simultaneously in a one-pot reaction with a polyamine having a molecular weight between 600 Da and 1800 Da, preferably PEI, and in a reaction time such that 0.90-1.33% N, preferably 1.00-1.28% N, particularly preferably 1.15-1.25% N, reacts on the polymer material, followed by step d), a column material with a comparable capacity is obtained, but a change in selectivity is obtained, with DCA and NO2 being preferred. - This results in the coelution of
[0028] In addition, ClO2 - , MCA, BrO3 - Since complete separation of , and MBA is not possible, the above two one-pot procedures result in ion exchangers that are not suitable for separation of all five haloacetic acids, inorganic standard ions and oxohalides in gradient elution with KOH.
[0029] Preferably, the compound used in step c) is of formula I
[0030] [ka]
[0031] It is of the following. R may be a linear or branched alkyl group or an ether group. It is possible to provide an ether group having one or more ether moieties, preferably two ether moieties.
[0032] R1, R2, or R3 may be independently selected from the group consisting of substituted or unsubstituted alkyl, substituted or unsubstituted heteroalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted heterocycloalkyl, or a 5- or 6-membered heterocycle formed between R1 and R2, or between R2 and R3, or between R1 and R3.
[0033] X may be a functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group or a halide, but other reactive groups such as tosylates or mesylates are also possible.
[0034] Advantageously, the compound is of formula I, where R is -(CH2) n -or-(CH2) n -O-(CH2) n - (wherein n is selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10), and R1, R2, and R3 are each or independently selected from the group consisting of linear or branched alkyl groups or ether groups consisting of: - -CH3 and -(CH2) n an alkyl group selected from the group consisting of -CH3, where n is selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10; or an alkyl alcohol group selected from the group of linear or branched alkyl alcohols, preferably -(CH2) n an alkyl alcohol group selected from the group consisting of -OH (n=1, 2, 3, 4, 5, 6, 7, 8, 9, 10); may be also possible.
[0035] The compound may be of formula II, formula III, or formula IV
[0036] [ka]
[0037] (Wherein, R is -(CH2) n -or-(CH2) n -O-(CH2) n - (wherein n is selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10), selected from linear or branched alkyl or ether groups. It may be of the following type.
[0038] Preferably, the compound used in step c) is of formula (I) selected from the group consisting of glycidyltrimethylammonium chloride; glycidylmethyldiethanolammonium chloride; and glycidyltriethylammonium chloride.
[0039] Preferably, the compound used in step c) is a (halogenoalkyl)trialkylammonium halide selected from the group consisting of (3-chloro-2-hydroxypropyl)trimethylammonium chloride, (2-chloroethyl)trimethylammonium chloride, (2-bromoethyl)trimethylammonium bromide, (3-bromopropyl)trimethylammonium bromide, (5-bromopentyl)trimethylammonium bromide.
[0040] A crosslinking step d) can follow step c) of the method. As outlined above, the reaction product resulting from step c) can contain one or more polyfunctional compounds, in particular at least one first functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups, and - at least one second functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups; The compound may be treated with
[0041] In this case, the polyfunctional compound(s) is preferably epoxides, in particular 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, poly(ethylene glycol) diglycidyl ether, resorcinol diglycidyl ether, glycerol diglycidyl ether, glycidol; - halogenated alkanes, in particular epichlorohydrin, epibromohydrin, 1,1'-oxybis[2-(2-chloroethoxy)ethane], 1,2-bis(2-chloroethoxy)ethane, bis(2-chloroethyl)ether, 1-chloro-3-iodopropane, 1,4-dibromobutane, 1,3-dibromopropane; - Aldehydes, especially glutaraldehyde is selected from.
[0042] The effect of this step is to show a significant shift in selectivity in the chromatograms obtained with these ion exchangers. - / NO3 - and DCA / ClO3 - is achieved using the polymer support obtained in step d) as ion exchange material in KOH eluent. The advantage of BDDGE is its hydrophilicity, which allows tuning the selectivity of ions in the chromatogram.
[0043] Alternatively, the effect may be achieved if the crosslinking step with a polyfunctional compound is replaced by a step of treating the reaction product from step c) with one or more monofunctional compounds, in particular compounds having functional groups reactive with amines and / or hydroxy groups. The monofunctional compound(s) is / are preferably selected from the group consisting of substituted or unsubstituted alkyl, substituted or unsubstituted heteroalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted heterocycloalkyl, and most preferably selected from halogenoalkanes or epoxyalkanes, in particular iodooctane or 1,2-epoxyoctane.
[0044] PEI can be covalently attached to the support material. This results in a polymeric material that is stable up to a pH of 14. Preferably, PEI is attached to the support material, which is preferably a polymeric support material, by a spacer molecule.
[0045] The spacer molecule may be a multifunctional molecule having groups that are reactive with alcohols / amines (substrate functionality) and other groups that are reactive with polyamines.
[0046] Preferably, the support material provided in step a) comprises groups which are reactive with the spacer molecules on the substrate surface.
[0047] For the purposes of the present invention, spacer molecule (or spacer), as previously mentioned, means a molecule comprising at least two functional groups, which ensures a space of at least 3 atoms, preferably 3 to 20 atoms, between the support and the oligo- or polyamine, preferably PEI. The functional groups of the spacer molecule may be functional groups susceptible to nucleophilic attack by OH or amine groups, such as halogenated hydrocarbons, epoxides, tosylates, methylsulfides, or combinations thereof. The spacer atoms may be constructed by carbon atoms, but the carbon chain may also include heteroatoms to provide ether or thioether groups. The spacer molecule creates a space between the support and the outer layer of the polymer, monomer, or modification, such as an ion exchange group. The spacer molecule prevents interactions between the analyte and the polymeric support substrate, thus reducing undesired peak broadening in the chromatograms obtained with the above polymeric support materials. Carbon chains spaced with ether groups are preferred due to their higher hydrophilicity. As an example, the spacer can have a glycidyl group that is reactive with amine and / or hydroxy groups, such as 1,4-butanediol diglycidyl ether.
[0048] Preferably, the support material provided in step a) contains groups which are reactive with epoxides, in particular hydroxyl groups.
[0049] The support material provided in step a) may be selected from the group consisting of: hydrocarbon-based compounds, in particular aromatic hydrocarbon-based compounds; PVA; sugar-based compounds; inorganic compounds, in particular silica, zirconia, alumina, titania.
[0050] To allow the possibility of using the prepared materials in suppressed ion chromatography mode, the support particles should be compatible with high hydroxide eluents with a pH of up to 14. For this reason, the most suitable support particles are aromatic divinylbenzene-based copolymers with a high degree of crosslinking (defined by the DVB monomer content). However, the high hydrophobicity of such aromatic substrates requires a hydrophilization procedure to be carried out in order to achieve better column efficiency and to introduce anchor groups for the attachment of functional layers. A procedure combining both aspects is disclosed in PCT / EP2020 / 059908.
[0051] The method further comprises, prior to step b), - Oxidation treatment of the polymer support substrate; and then - Reduction or hydrolysis treatment The method may include the step of generating hydroxy groups on / in the support material by a process including the steps of:
[0052] The oxidation treatment may be a treatment with a peracid, preferably selected from the group of metachloroperbenzoic acid, performic acid, peracetic acid, peroxytrifluoroacetic acid, treatment with KMnO4, treatment with oxygen plasma, or a combination thereof.
[0053] By using peracid, the double bonds were oxidized, facilitating the subsequent reduction or hydrolysis. It goes without saying that this effect can also be achieved by other oxidation processes known to those skilled in the art, such as ozonolysis. It is particularly preferred that peracid is used, since a high oxygen content can be achieved. With oxygen plasma, an oxygen content of 2.0% at the surface of the support substrate can be achieved, as can be measured by elemental analysis, while with m-CPBA, for example, an oxygen content of 3.2% or more can be achieved. When peracid is used, it can be added to the polymer in suspension or formed in situ from acid and hydrogen peroxide. Preferably, m-CPBA is added to a suspended core polymer support substrate, such as a PS / DVB polymer substrate. An oxygen content of at least 2% can be achieved, as can be measured by elemental analysis.
[0054] In a preferred embodiment, the reduction treatment of the reaction products is carried out with a reagent for the reduction of polar bonds, preferably with a metal hydride. For example, NaBH4, BH3, LAH, NaH, CaH can be used. The use of hydrides has the advantage that the dissolved reagent can penetrate into the pores of the particles. This is not possible, for example, with palladium on activated carbon. Compared to hydrolysis with hydrochloric acid, which hydrolyzes epoxides to hydroxylenes, the reduction with metal hydrides can also convert carbonyls and carboxyls. The reduction converts the formed oxidation products into alcohols. Lithium aluminum hydride is preferably used in ether. For example, 5-100% w / w of lithium aluminum hydride polymer (dry) can be added to a 1-20% w / v polymer suspension in anhydrous tetrahydrofuran (THF). Preferably, 5-20% w / w of lithium aluminum hydride polymer (dry) can be added to a 5-15% w / v polymer suspension in anhydrous THF. Typical temperatures are in the range of 25 to 70° C., with the boiling point of THF being particularly preferred, and reaction times are from 1 minute to 72 hours, particularly preferably from 3 hours to 48 hours.
[0055] Advantageously, the reaction product obtained after the reduction or hydrolysis treatment is pressure stable at pressures below 220 bar, preferably below 250 bar, particularly preferably below 300 bar. Here, pressure stability is understood to mean that the pressure increase as a function of the flow rate is only linear. The good pressure stability is due to the small particle size and the microporosity / mesoporosity of the particle structure, as explained below.
[0056] The support material is preferably - derived in part from an aromatic hydrocarbon compound having at least two vinyl or allylic substituents, preferably derived at least in part from a divinylbenzene monomer; and - derived in part from a monomer selected from the group consisting of ethylvinylbenzene, vinyl acetate, styrene, and any combination thereof.
[0057] The relative amount of aromatic hydrocarbon compounds having at least two vinyl or allyl substituents, preferably divinylbenzene derived monomers, is preferably at least 50% by weight.
[0058] Such supports are essentially entirely derived from compounds that do not contain oxygen atoms, thus providing mechanically and chemically stable particle cores that are compatible with the high hydroxide eluents present in suppressed ion chromatography.
[0059] In a preferred embodiment, step c) or step d) of the method described above is followed by step e) of heating the functionalized and crosslinked material in an alkaline solution. This allows the selectivity and capacity of the ion exchange material from the previous step to be adjusted. The treatment, hereinafter referred to as removal, in particular consists of a step of heating the particles provided with exchange groups in an aqueous alkaline solution, particularly preferably in an aqueous solution of hydroxides or carbonates of alkali or alkaline earth metals, for example in a sodium hydroxide solution. The preferred concentration of NaOH is in the range of 0.1 to 5 mol / L of base, with 0.2 to 2 mol / L of base being particularly preferred. The reaction temperature may be 20 to 100° C., particularly preferred is 20 to 40° C., and the treatment time is 0.1 to 150 hours, particularly preferred is 12 to 24 hours.
[0060] The removal step alters the relative strength of interactions between the substrate and individual ions. In particular, secondary interactions with polarizable analytes can be reduced. The tailing of signal peaks observed due to such secondary interactions is reduced, and therefore polarizable ions are also eluted symmetrically. At the same time, the electrostatic interaction capacity of the column is also reduced after removal, decreasing the overall capacity of the ion exchange material.
[0061] A second aspect of the invention relates to a support material obtainable by the method described above, for use as a stationary phase in analytical or preparative processes, in particular chromatographic methods.
[0062] Advantageously, the support material provided in step a) is microporous and / or mesoporous.
[0063] It is particularly preferred that the claimed polymeric support is based on a polymeric support substrate that is microporous and / or mesoporous. It is particularly preferred that the polymeric support substrate is hydrophobic. In this specification, hydrophobic means that the polymeric support is non-polar, i.e. that there are no monomeric units with a dipole moment >0.2D. In this specification, microporous and / or mesoporous means that the polymeric support has an average pore size of at most 50 nm, which can be measured by nitrogen adsorption in the BJH model.
[0064] The support material is preferably present as particles, more preferably as spherical particles, particularly preferably having an average particle size of 1 to 50 μm, more preferably an average particle size of 2 to 25 μm, particularly preferably an average particle size of 3 to 9 μm. In this specification, particle size is defined as the average value between the longest and shortest straight lines passing through the center of the particle, which can be measured by scanning electron microscopy (SEM) and automated image evaluation.
[0065] The size of the particles can be adjusted by suitable stirring speed, choice of solvent, concentration of polymer in the solvent, etc. Procedures are known to the skilled person. A polymer support of this shape and size has a volume / surface ratio that has been found to be particularly advantageous for exchange capacity. It exhibits high diffusivity in the pores and is easy to fill.
[0066] Preferably, the polymeric support is stable in the pH range 0-14 such that the difference between the retention time of sulfate ions in the packed column after one rinse, in particular with 1 M NaOH solution and / or one rinse with 1 M HNO3 solution, and the retention time of sulfate ions before such rinse does not exceed 8%, preferably does not exceed 5%, particularly preferably does not exceed 3%. The method for measuring pH stability is carried out as follows: the sample is loaded into the chromatography column and the retention time of sulfate ions is determined from 10 measurements with an eluent of Na2CO3 6 mmol / L and NaHCO3 1 mmol / L. The column is then rinsed with an eluent of Na2CO3 6 mmol / L and NaOH 1 mol / L (pH 14) at 0.8 mL / min for 14 hours. Then, 10 additional measurements of sulfate ion retention time are carried out with an eluent of Na2CO3 6 mmol / L and NaHCO3 1 mmol / L. The column is then flushed with an eluent of Na2CO3 6 mmol / L and HNO3 1 mol / L (pH 0) at 0.8 mL / min for 14 h. Then 10 additional measurements of sulfate retention time are performed with an eluent of Na2CO3 6 mmol / L and NaHCO3 1 mmol / L. Each time, the eluent is changed and the column is rinsed with water for 1 h to avoid precipitation. Possible changes are investigated based on the retention time and plate number of sulfate; both parameters deviated by a maximum of 3% from the originally determined values after both basic and acidic treatments.
[0067] The polymer support material as described above is - monomer units derived from aromatic hydrocarbon compounds having at least two vinyl or aryl substituents, preferably monomer units derived from divinylbenzene; - monomer units derived from ethylvinylbenzene; - monomer units derived from styrene; - The combination The polymeric support substrate may be composed substantially entirely of monomer units selected from the group consisting of:
[0068] "Consisting essentially entirely of" means that the total proportion of the recited monomer units in the polymeric support material provided in step a amounts to at least 95% by weight, preferably at least 98% by weight, particularly preferably at least 99% by weight. In other words, the monomer units can be derived essentially entirely from compounds that do not contain oxygen atoms, thus resulting in a hydrophobic particle core.
[0069] The polymer support substrate can have an average pore radius of 1 to 50 nm, preferably an average pore radius of 2 to 25 nm, particularly preferably an average pore radius of 2 to 10 nm, which can be measured by nitrogen adsorption in a BJH model. The measurement is carried out as described in the examples.
[0070] Preferably, the polymer support substrate has a specific surface area of 80 to 1000 m, which can be measured by nitrogen adsorption in the BET model. 2 / g, preferably with a specific surface area of 100 to 800 m 2 / g, and even more preferably a specific surface area of 200 to 600 m 2 / g. The measurement is carried out as described in the examples.
[0071] A high specific surface area increases the capacity and resolution of the column, especially when separating small ions such as common ions.
[0072] Modification of the polymeric support substrate to obtain the support material as provided in step a) of the method is described in PCT / EP2020 / 059908, the contents of which are incorporated herein by reference in their entirety.
[0073] The present invention is based at least in part on the idea that the material, as described in PCT / EP2020 / 059908, can be further improved by coating with an oligoamine or polyamine, in particular polyethyleneimine PEI, to reduce the effect of the oxygen content of the support particles on the selectivity and thus simplify the control of the batch-to-batch reproducibility of the entire modification procedure. The coating with PEI provides additional protection to the substrate, thus reducing interactions with the underlying surface. At the same time, the present invention shares the advantages of PCT / EP2020 / 059908, such as high chemical and mechanical stability, as well as good column performance, while offering the possibility to control the selectivity and column capacity independently of each other at the various modification steps.
[0074] The polymeric support substrate may typically be provided as particles, preferably as spherical particles, particularly preferably as spherical particles having an average particle size (median) of 1 to 50 μm, even more preferably an average particle size of 2 to 25 μm, particularly preferably an average particle size of 3 to 9 μm. However, other polymeric supports are also envisaged, in particular polymeric supports in the form of membranes or monoliths. By spherical, it is meant that the particles have a sphericity value of
[0075]
number
[0076] means having a molecular weight of at least 0.80, preferably at least 0.90, more preferably at least 0.95, wherein V p is the volume of the particle and Ap is the surface area of the particle.
[0077] The oxygen content of the surface of the polymeric support can be increased by initial oxidation and reduction or hydrolysis. By modification, hydroxy groups can be initially generated on / in a core polymeric support substrate that has no detectable oxygen content. The increased oxygen content can affect the type and characteristics of secondary interactions, especially the hydrophilicity of the resulting polymeric support. By a series of steps following the initial oxidation and reduction / hydrolysis, the capacity can be adjusted independently of the surface oxygen content.
[0078] The surface of the polymeric support or the polymeric support surface is understood herein to mean in particular the outer surface of the polymeric support structure and the layer of 1 to 30 nm directly adjacent to this outer surface that can be contacted by the solution. The outer surface that can be contacted by the solution can be partially arranged in a microstructure, for example a porous microstructure. In particular, the outer surface of the polymeric support substrate particle having a porous or non-porous structure that can be contacted by the solution is envisaged.
[0079] The first contribution to chemical and mechanical stability can be made by the covalent bond between the polymer support and the coating. This is in contrast to the use of latex-based ion exchangers, where pure electrostatic interactions result in the position and orientation of the exchange groups relative to the substrate. High chemical inertness is ensured by the covalent bond. The second contribution to mechanical stability can be made by the core polymer support being at least partially formed from an aromatic hydrocarbon compound, preferably having at least two vinyl or allyl substituents, and preferably at least partially formed from a divinylbenzene monomer. The stability of this core polymer support substrate is not affected by any pretreatment steps, such as oxidation and reduction and hydrolysis treatments. The core polymer support substrate is preferably monodisperse.
[0080] The advantage of the high robustness of the particles is particularly evident when a column packed with the polymeric support material obtained by the above method is subjected to a pressure-flow test. In the pressure-flow test, the change in pressure in the column is determined as a function of the continuously increasing flow rate of the mobile phase. In the column according to the invention, the pressure has a linear dependence on the flow rate. This is in contrast to the results obtained with a column packed with a conventional hydrophilic pDVB matrix with a significant vinyl acetate content. For conventional columns, the pressure increases more than linearly as the flow rate increases. For example, a hyperbolic function can result. This is shown, for example, in the literature by Caglayan et al. (J Sep Sci 2006, vol. 29, p. 940). According to the literature, when a column packed with such a matrix is subjected to an increased flow rate, a sharp increase in back pressure is caused by the increased amount of vinyl acetate-derived monomers and therefore the increased amount of OH groups in the hydrolyzed particle matrix.
[0081] A third aspect of the invention relates to a chromatography column, in particular an ion exchange chromatography column, packed with the support material described above.
[0082] A fourth aspect of the invention relates to a method for the chromatographic separation of analytes, in which a solution containing the analytes is contacted with a polymeric support material modified as described above, in particular passed through a chromatographic column according to one aspect of the invention.
[0083] A fifth aspect of the invention relates to the use of a polymeric support material as described above and / or obtainable by a method as described above for the analysis or preparative separation of analytes, in particular for use in anion exchange chromatography, cation exchange chromatography and / or HILIC chromatography. The polymeric support material is particularly suitable for use in suppressed ion chromatography.
[0084] The present invention will be more fully understood from the following examples, however, those of ordinary skill in the art will recognize that modifications are possible and are well within the scope of the present disclosure. [Brief description of the drawings]
[0085] [Figure 1] FIG. 1 is a schematic diagram of a PEI-modified substrate. [Diagram 2] FIG. 1 is a schematic diagram of modification with a compound that exposes ion-exchange groups. [Diagram 3] FIG. 1 is a schematic diagram of modification by a cross-linking step. [Figure 4] FIG. 6 shows a chromatogram obtained on the polymer support according to example 6.2 in isocratic mode. [Diagram 5] FIG. 5 shows the variation of retention factor k′ depending on the amount of GTMA used in Example 5.1. [Figure 6A] FIG. 1 shows chromatograms comparing the performance of polymer supports according to Example 5.1 and Example 6.1. [Figure 6B] FIG. 1 shows chromatograms comparing the performance of polymer supports according to Example 5.1 and Example 6.1. [Figure 7A] FIG. 2 shows a chromatogram of the polymer support according to Comparative Example A in separating certain specific ions. [Figure 7B] FIG. 2 shows a chromatogram of the polymer support according to Comparative Example A in separating certain specific ions. [Figure 8A] FIG. 6 shows comparative chromatograms obtained on the polymer support according to example 6.2 with low and high crosslinking degrees of the coating. [Figure 8B] FIG. 6 shows comparative chromatograms obtained on the polymer support according to example 6.2 with low and high crosslinking degrees of the coating. [Figure 9] FIG. 6 shows a chromatogram obtained by using the polymer support according to Example 6.2 in gradient mode. [Figure 10] FIG. 2 shows the pressure-flow profile measured on a chromatography column packed with the polymeric support of the invention according to step a). [Figure 11] FIG. 1 shows the results of particle size analysis by SEM (number per diameter [μm]). [Figure 12] FIG. 5 shows a chromatogram of the polymer support according to Example 14 in separating the same ions as in FIG. 4. Example 1
[0086] Example 1: Providing a polymeric support substrate Polystyrene seed particles were prepared by dispersion polymerization of styrene in ethanol, stabilized with polyvinylpyrrolidone and initiated with azo-bis-iso-butyronitrile. Thus, polystyrene particles with an average diameter of 1.5 μm (Mn=15 kg / mol, Mw=55 kg / mol) were obtained. Polymerization, stabilized with polyvinyl alcohol and initiated with azo-bis-iso-butyronitrile, was continued in a water / isoamyl alcohol emulsion of 55 wt % divinylbenzene (DVB), 45% ethylvinylbenzene (EVB), and toluene. Thus, an average radius of 4.6 μm and a specific surface area of 540 m 2 / g, and porosity 1 cm 3 Porous, highly crosslinked poly(DVB-EVB) particles having a molecular weight of 1.0 / g were obtained.
[0087] Example 1.1: Determining the average pore radius and specific surface area of a polymeric support substrate The average pore radius of the starting polymer support substrate was determined by nitrogen adsorption in the BJH (Barret, Joyner, Halenda) model. The specific surface area was determined by nitrogen adsorption in the BET model (Brunauer, Emmett, Teller). For both analyses, a sample of 0.10945 g of PS / DVB polymer support substrate was used. The density of the sample material was 1.105 g / cc. The measurements were performed in a 9 mm cell on an Autosorb iQ S / N:14713051301 instrument. The bath temperature was 77.35 K. The final degassing temperature was 60° C. The evaluation of the measurements was performed with Quantachrome ASiQwin version 3.01. The measurements were performed twice, once with an immersion time of 80 min and once with an immersion time of 40 min. The outgassing rates were 1.0° C. / min and 20.0° C. / min, respectively. The average pore radius obtained from the BJH method based on pore volume was 5.1060 nm. The specific surface area from the multipoint BET plot was 540.0 m 2 / g.
[0088] Example 1.2: Determining the pressure stability of a polymer support Oxidation with hydrogen peroxide and reduction with lithium aluminum hydride were performed on the original polymer support substrate. The obtained particles were subjected to a pressure test. For the pressure test, a 250 x 4 mm column was packed with the particles and water was passed through the column at increasing flow rates. Figure 10 shows the pressure-flow profile measured at room temperature. The y-axis shows the system pressure (bar). The x-axis shows the flow rate (mL / min). Eight intervals of 30 seconds each were measured, increasing the flow rate in steps from 0.2 ml / min to 1.6 ml / min. As can be seen, the pressure depends linearly on the flow rate up to a pressure of 400 bar or 40 MPa.
[0089] Example 1.3: Steps for determining average particle size Circularity and average particle size were determined for a sample of the initial polymer support prepared in step a. The sample was applied to a scanning electron microscope carrier with a single particle layer and coated with gold using a sputter coater of LOT type AutomaticSputterCoater MSC1 connected to a Vacubrand RZ6 vacuum pump. A series of 27 images was taken using a scanning electron microscope (Phenom ProX) and individual particles were identified and measured using an Olympus Imaging Solutions Scandium. The identified particles were analyzed for spherical diameter and roundness. All images were analyzed in a batch process with the same threshold and the same measurement settings. A total of 6039 particles with a circularity of ≧0.8 were measured. The measurement results are shown in FIG. 11, which shows the number of particles on the y-axis and the diameter (μm) on the x-axis. The smallest measured radius was 0.8 μm and the largest was up to 10 μm. The average diameter (median) was 4.6 μm with a relative standard deviation of 6.2%. The polydispersity index PDI (Mw / Mn) was found to be 1.04. Example 2
[0090] Example 2.1: Hydroxy group generating step Oxidation with acetic acid: 61.7 g of the product from Example 1 was suspended in 382 mL of acetic acid in a 1 L reactor connected to a thermostat. The reaction mixture was heated to 80° C. 121 mL of hydrogen peroxide (35%) was slowly added. The reaction mixture was stirred for 24 hours, then cooled and filtered. The filter cake was washed with ultrapure water to neutral pH and rinsed with ethanol. The filter cake was dried in a vacuum oven to give 66 g of product.
[0091] Reduction with lithium aluminum hydride: 51.7 g of the dried oxidation product was suspended in 196 mL of anhydrous THF in a 1 L reactor and cooled to 5° C. using a thermostat. 92 ml of a 2.4 M solution of lithium aluminum hydride in THF was carefully added with stirring. The reaction mixture was heated to 55° C. and stirred for 48 h. The reaction was stopped by cooling to 0° C. within 60 min and adding 80 ml of water. The reaction mixture was then diluted and 150 ml of sulfuric acid was added with stirring. The reaction mixture was heated to 80° C. for 1 h and then filtered. It was washed with water to neutral pH and rinsed with acetone. The filter cake was dried to yield about 50 g of product. The whole procedure was repeated twice.
[0092] Example 2.2: Hydroxy group generating step: Oxidation with acetic acid: 41 g of the product of Example 1 was suspended in 300 mL of acetic acid in a 1 L reactor equipped with a thermostat. The reaction was heated to 80° C. 79 mL of hydrogen peroxide (35%) was added slowly within 2 hours. The reaction mixture was stirred for 18 hours, then another portion of 79 ml of hydrogen peroxide was added and the mixture was stirred for another 4 hours. The reaction mixture was cooled, filtered, washed with ultrapure water until neutral pH and rinsed with ethanol. The filter cake was dried in a vacuum oven to give 45.1 g of oxidation product.
[0093] Reduction with lithium aluminum hydride: 41.3 g of the dried oxidized product was suspended in 434 mL of anhydrous THF in a 1 L reactor and cooled to 0° C. using a thermostat. 5.1 g of lithium aluminum hydride was carefully added with stirring. The reaction mixture was heated to 55° C. and stirred for 20-24 h. The reaction was stopped by cooling to 0° C. within 60 min and adding 300 ml of water. The reaction mixture was then filtered, the residue was resuspended and 41.3 ml of 32% hydrochloric acid was added with stirring. The reaction mixture was heated to 80° C. overnight, then filtered, washed with water to neutral pH and rinsed with acetone. The filter cake was dried to yield about 39.8 g of product. The whole procedure was repeated twice. Example 3
[0094] Example 3.1: Providing a terminal epoxy group on a linker 25 g of the reaction product of Example 2.1 was suspended in 93.75 mL of dimethyl sulfoxide and 65.5 mL of 1,4-butanediol diglycidyl ether. The flask was subjected to three vacuum / argon cycles. Under constant stirring, 37.5 mL of NaOH (0.6 M in water) was added and the reaction mixture was stirred at 28° C. for 26 hours. The product was filtered and washed with water and ethanol.
[0095] Example 3.2: Providing a terminal epoxy group on a linker 10 g of the reaction product of Example 2.2 was suspended in 37.5 mL of dimethyl sulfoxide and 25 mL of 1,4-butanediol diglycidyl ether. The flask was subjected to three vacuum / argon cycles. Under constant stirring, 25 mL of NaOH (0.6 M in water) was added and the reaction mixture was stirred at 28° C. for 22 hours. The product was filtered and washed with water and ethanol. Example 4
[0096] Example 4.1: Preparing a PEI layer The product of Example 3.1 (substrate) was suspended in a mixture of ethanol and water. Polyethylenimine PEI (CAS25987-06-8) was dissolved in water, stirred and sonicated. The suspended particles and dissolved PEI were combined and stirred at 60° C. for 23.5 hours. The weight ratio of PEI to substrate used was 0.4 g per 1 g. The product was filtered and washed with water. A schematic diagram of the synthesis is shown in FIG. 1.
[0097] Example 4.2: Preparing a PEI layer The procedure was the same as in Example 4.1, but using the product of Example 3.2 as the substrate. A schematic diagram of the synthesis is shown in Figure 1. Example 5
[0098] Example 5.1: Step of introducing ion exchange groups The finished product of Example 4.1 was suspended in ethanol / water, stirred and sonicated. Glycidyl trimethylammonium chloride (GTMA, CAS3033-77-0) was added and the reaction mixture was stirred at 60° C. for 4 hours. The weight ratio of GTMA used to substrate was 3.2 g per 1 g. The product was filtered and washed with water. A schematic diagram of the synthesis according to Example 5.1 is shown in FIG. 2.
[0099] Example 5.2: Step of introducing ion exchange groups The procedure was the same as in Example 5.1, but the product of Example 4.2 was used as the substrate, and the amount of GTMA used was 0.8 g per 1 g of substrate. A schematic diagram of the synthesis is shown in Figure 2. Example 6
[0100] Example 6.1: Cross-linking step The finished reaction product of Example 5.1 was suspended in water. 1,4-butanediol diglycidyl ether (1,4-BDDGE, CAS2425-79-8) was added and the mixture was stirred at 60°C for 2.5 hours. The weight ratio of 1,4-BDDGE to substrate used was 2 ml per gram. The product was filtered and washed with water. A schematic diagram of the synthesis according to Example 6 is shown in Figure 3.
[0101] Example 6.2: Cross-linking step The procedure was the same as in Example 6.1, but the product of Example 5.2 was used as the substrate. A schematic diagram of the synthesis is shown in Figure 3. Example 7
[0102] Example 7: Ion Chromatography A 250 x 4 mm column was packed with the ion exchange material obtained according to Example 6.2 and solutions of fluoride, acetate, formate, chlorite, bromate, chloride, nitrite, dichloroacetate, chlorate, bromide and nitrate were passed through the column at 20°C and a flow rate of 0.8 ml / min using 9 mM KOH as the mobile phase. Figure 4 shows the chromatogram obtained using such a column. The ions elute separately, giving rise to distinct, narrow peaks. Example 8
[0103] Example 8: Capacity Control The variability of the capacity of the ion exchange material was brought about by using different amounts of GTMA in the procedure according to Example 5.1. The effect of changing the amount of GTMA used (0.4 g, 0.8 g, 1.6 g, and 3.2 g) was established by measuring the retention coefficient k' of all inorganic analytes from Example 7, which depend on it. The results are shown in Figure 5. As can be seen from Figure 5, the retention of monovalent ions depends linearly on the amount of GTMA added, which allows the control of the capacity of the column. At the same time, it was shown that the selectivity of all manufactured ion exchangers for the tested analytes (measured as the retention coefficient of the analyte divided by the retention coefficient of the chloride ion) was almost the same (relative standard deviation <5%) regardless of the capacity, suggesting that the capacity does not affect the column selectivity for inorganic anions. Example 9
[0104] Example 9: Effect of substrate and linker on selectivity The selectivity coefficients for all analytes from Example 7, except for dichloroacetate ion, compared to chloride ion were determined using KOH as eluent and compared for ion exchange materials prepared according to Example 6.1 and Example 6.2. For preparing materials according to Example 6.2, substrates obtained according to Example 3.2 were used when the reaction was carried out for 16, 19, 22 and 23.5 hours, resulting in different lengths and different densities of linkers for polyamine binding. The selectivity coefficients for all analytes were almost the same in all cases, with a relative standard deviation of less than 5%, suggesting that the variability introduced in the previous steps or any potential variability in substrate modification degree and linker length and density in the large-scale manufacturing process does not significantly affect the selectivity. Example 10
[0105] Example 10: Effect of cross-linking The crosslinking step (see Example 6.1) was described above as beneficial to the performance of ion exchangers based on materials according to the invention. A comparative study was carried out of separation columns (250x4) packed with ion exchanger materials from Example 5.1 and Example 6.1, respectively. The analytes were fluoride, acetate, formate, chlorite, bromate, chloride, nitrite, dichloroacetate (DCA), chlorate, bromide, nitrate (KOH eluent, 40 mM, 1.0 ml / min). Figure 6A shows a chromatogram obtained by using the material from Example 5.1. Figure 6B shows a chromatogram obtained by using the polymeric support from Example 6.1. Crosslinking allows the DCA / chlorate and bromide / nitrate ion pairs to be separated and eluted separately.
[0106] Comparative example A: The polymeric support was prepared according to the teachings of Example 4 of EP 3721998, except that N-methylpyrrolidone was replaced with the same amount of N-methylmorpholine. Figure 7A shows a chromatogram obtained by using the material according to Comparative Example A, using a KOH eluent. Figure 7B shows a chromatogram obtained by using the polymeric support according to Comparative Example A in the presence of other functionalities (NMP, MDEA). As can be seen, when using the polymeric support according to Comparative Example A, the various ions of interest are often co-eluted. Example 11
[0107] Example 11: Selectivity control: The cross-linking step (see Example 6.2) was described above as beneficial to the performance of ion exchangers based on materials according to the invention. A low degree of cross-linking requires the use of polymeric supports in gradient elution mode due to the slow elution of polyvalent anions. A high degree of cross-linking allows the use of polymeric supports in isocratic elution mode. This step is therefore relevant for the control of column selectivity. A comparative study was carried out of separation columns (250x4) filled with ion exchanger materials obtained according to Example 6.2 with a high degree of cross-linking ensured by a long reaction time (25 hours) and a low degree of cross-linking obtained by a short reaction time (2.5 hours). The analytes were fluoride, acetate / glycolate, formate, chlorite, bromate, chloride, nitrite, dichloroacetate, chlorate, bromide, nitrate, sulfate and phosphate, and KOH was used as eluent. Figure 8A shows a chromatogram obtained by using a polymeric support material with a low cross-linking degree of coating while using gradient elution (increasing the KOH concentration during the analysis). Figure 8B shows a chromatogram obtained by using a polymeric support material with a high cross-linking degree while using isocratic elution. Both chromatograms allow for clear, distinct separation of the analyte ions of interest, but the material with a high cross-linking degree allows for faster elution of multiply charged anions and does not require the use of a gradient. Example 12
[0108] Example 12: Batch Variability Example 12 Three different batches of the polymeric support according to Example 6.1 were synthesized. Three columns (250 x 4 mm) were packed and the mixture of analytes described in Example 7 was separated in suppressed ion chromatography mode using KOH as eluent. The relative standard deviation (RSD) of the retention times of all analytes was less than 5%, suggesting good batch-to-batch reproducibility of the material. Example 13
[0109] Example 13: Separation of inorganic standard ions and haloacetic acids The polymeric support according to the invention can serve as the basis for producing an anion exchanger that allows the separation of five haloacetic acids, in addition to inorganic standard ions and oxohalides, preferably by using gradient elution with KOH. Figure 9 shows a chromatogram obtained by using a polymeric support according to Example 6.2. A separation column (250x4) filled with such an ion exchanger material was prepared, and an analyte solution containing inorganic standard ions (F, Cl, ClO2, ClO3, Br, BrO3, NO2, NO3, PO4, SO4) as well as acetate, formate, and five haloacetic acids (MCA, MBA, DCA, DBA, and TCA) was passed through said separation column using gradient elution mode with KOH as eluent (suppressed ion chromatography mode). As can be seen from Figure 9, all analytes elute separately and give clear peaks. Example 14
[0110] Example 14: Effect of Varying the Order of Steps d) and c) The finished product of Example 4 (PEI-bound) was treated according to Example 6 (BDGE) followed by treatment according to Example 5 (GTMA). Figure 12 shows the chromatogram obtained by using the polymeric support of Example 14. As can be seen, when using the polymeric support according to Example 14, there is co-elution of all ions of interest (same ions as in Figure 4).
Claims
1. A method for modifying a support material, particularly a polymeric support material, for use as a stationary phase in an analytical or preparative process, comprising the steps of: a) providing a support; b) coating said support with an oligoamine or polyamine; c) the support material a first functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups, and ion-exchange groups, preferably quaternary organic elements of main group V, preferably quaternary ammonium groups and reacting the compound with Including, The method, wherein steps b) and c) are carried out sequentially or simultaneously.
2. Step c) is followed by a crosslinking step. d) treating the reaction product resulting from step c) with one or more polyfunctional compounds, in particular at least one first functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups, and at least one second functional group, preferably an epoxy group, which is reactive with amine and / or hydroxy groups; with a compound having the formula: The method of claim 1 , further comprising:
3. 3. The method according to claim 1 or 2, wherein the oligoamine or polyamine in step b) is selected from the group consisting of polyallylamine, linear or branched polyethyleneimine (PEI), poly(2-methylaziridine), preferably branched PEI.
4. The compound used in step c) is represented by formula I 【Chemistry 1】 (In the formula, R is a linear or branched alkyl or ether group; Each of R1, R2, or R3 is independently selected from the group consisting of substituted or unsubstituted alkyl, substituted or unsubstituted heteroalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted heterocycloalkyl, or a 5- or 6-membered heterocycle formed between R1 and R2, or between R2 and R3, or between R1 and R3; X is a functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group or a halide. The method according to any one of claims 1 to 3, wherein
5. The compound is of formula I, wherein R is -(CH 2 ) n - or - (CH 2 ) n -O-(CH 2 ) n - (wherein n is selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10); wherein R1, R2, and R3 each or independently represent: - -CH 3 and -(CH 2 ) n -CH 3 where n is selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10; or an alkyl alcohol group selected from the group of linear or branched alkyl alcohols, preferably -(CH 2 ) n an alkyl alcohol group selected from the group consisting of -OH (n=1, 2, 3, 4, 5, 6, 7, 8, 9, 10); The method according to claim 4, wherein
6. The compound is represented by Formula II, Formula III, or Formula IV 【Chemistry 2】 (Wherein, R is -(CH 2 ) n - or - (CH 2 ) n -O-(CH 2 ) n - (wherein n is selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10), The method of claim 4,
7. 5. The method of claim 4, wherein the compound used in step c) is of formula (I) selected from the group consisting of glycidyl trimethyl ammonium chloride; glycidyl methyl diethanol ammonium chloride; and glycidyl triethyl ammonium chloride.
8. The compound used in step c) is (3-chloro-2-hydroxypropyl)trimethylammonium chloride, (2-chloroethyl)trimethylammonium chloride, (2-bromoethyl)trimethylammonium bromide, (3-bromopropyl)trimethylammonium bromide, (5-Bromopentyl)trimethylammonium bromide 5. The method of claim 4, wherein the (halogenoalkyl)trialkylammonium halide is selected from the group consisting of:
9. The polyfunctional compound(s) used in step d) epoxides, in particular 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, poly(ethylene glycol) diglycidyl ether, resorcinol diglycidyl ether, glycerol diglycidyl ether, glycidol; halogenated alkanes, in particular epichlorohydrin, epibromohydrin, 1,1'-oxybis[2-(2-chloroethoxy)ethane], 1,2-bis(2-chloroethoxy)ethane, bis(2-chloroethyl)ether, 1-chloro-3-iodopropane, 1,4-dibromobutane, 1,3-dibromopropane; - aldehydes, in particular glutaraldehyde The method according to any one of claims 2 to 8, wherein the
10. 2. The method according to claim 1, wherein the reaction product resulting from step c) is treated with one or more monofunctional compounds, in particular compounds having a functional group reactive with amines and / or hydroxy groups, said monofunctional compound(s) being preferably selected from the group consisting of substituted or unsubstituted alkyl, substituted or unsubstituted heteroalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted heterocycloalkyl, most preferably selected from halogenoalkanes or epoxyalkanes, in particular iodooctane or 1,2-epoxyoctane.
11. 11. The method according to any one of claims 1 to 10, wherein the PEI is covalently attached to the support material, preferably the PEI is attached to the support material, preferably a polymeric support material, by a spacer molecule.
12. The method of claim 11 , wherein the spacer molecule is a multifunctional molecule having groups that are reactive with alcohols / amines and other groups that are reactive with polyamines.
13. The method of claim 12 , wherein the support material provided in step a) comprises groups that are reactive with the spacer molecules at the substrate edges.
14. 14. The method according to any one of claims 1 to 13, wherein the support material provided in step a) comprises groups reactive with epoxides, in particular hydroxyl groups.
15. 15. The method according to any one of claims 1 to 14, wherein the support material provided in step a) is selected from the group consisting of: hydrocarbon-based compounds, in particular aromatic hydrocarbon-based compounds; PVA; sugar-based compounds; inorganic compounds, in particular silica, zirconia, alumina, titania.
16. Before step b), - an oxidation treatment of said support material; and then - Reduction or hydrolysis treatment 16. The method of claim 1 , further comprising the step of generating hydroxy groups on / in the support material by a process comprising the steps of:
17. The support material is - derived in part from an aromatic hydrocarbon compound having at least two vinyl or allylic substituents, preferably derived at least in part from a divinylbenzene monomer; and - derived in part from monomers selected from the group consisting of ethylvinylbenzene, vinyl acetate, styrene, and any combination thereof; The relative amount of aromatic hydrocarbon compounds having at least two vinyl or allyl substituents, preferably divinylbenzene derived monomers, is preferably at least 50% by weight.
17. The method according to any one of claims 1 to 16, characterized in that
18. Following step c) or step d), step e) heating the functionalized and cross-linked material in an alkaline solution The method according to any one of claims 1 to 17, further comprising:
19. 20. A support material obtainable by the method according to any one of claims 1 to 18 for use as a stationary phase in analytical or preparative processes, in particular chromatographic methods.
20. 20. The support material of claim 19, wherein the support material provided in step a) is microporous or mesoporous.
21. In particular, one rinse with 1M NaOH solution and / or 1M HNO 3 21. The support material according to claim 19 or 20, wherein the material is stable in the pH range 0 to 14 such that the difference between the retention time of sulfate ions in the packed column after one rinsing with a solution and the retention time of sulfate ions before such rinsing does not exceed 8%, preferably does not exceed 5%, particularly preferably does not exceed 3%.
22. 22. A chromatography column, in particular an ion exchange chromatography column, packed with a support material according to any one of claims 19 to 21.
23. 23. A method for the chromatographic separation of an analyte, characterized in that a solution containing said analyte is contacted with a polymeric support material according to any one of claims 19 to 21, in particular through a chromatographic column according to claim 22.
24. 22. Use of a polymeric support according to any one of claims 19 to 21 and / or a polymeric support obtainable by the method according to any one of claims 1 to 21 for the analysis or fractionation of analytes, in particular for use in anion exchange chromatography, cation exchange chromatography and / or HILIC chromatography.